Cardiac arrhythmia spot light: Detection of ventricular fibrillation—Not all ICDs are created equal. Issue 4 (19th May 2021) - Lee, Adam; Salazar, James W.; Tseng, Zian H.
Abstract : Intracardiac device electrograms demonstrating differing VF sensing performance between two manufacturer ICD generators.